(3TQM GdaQGFV GdSLGhfOjIs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s ((3TgQ fhGHQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eMeO Hf YHO GdQTjO GdSLGhfOj bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3JYdehG GdaQGFV hYdehgG GdfGS(B" (3gcPG QhGjI GdabgGA hGdaQGjV LeY aQjVI hgj eG bOQ ef GdSgGe aj GdejQGKs
(3BNQgG (B:s
(3ef UGMHg eG hQK efg abO GLJeY dCe cd efgeG YTQhf hdHfJg SJhf hdehdGg YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 514 (3, (B515s
(3cTa GdXfhf (B2 / 12487s
(3gOjI GdYGQajf (B1 / 728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs